Colour flow Doppler mapping in the assessment of prosthetic valve regurgitation. Issue 1 (July 1989) - Chambers, J; Monaghan, M; Jackson, G
Abstract : Two hundred Carpentier-Edwards, Björk-Shiley, and Starr-Edwards prostheses in 173 patients were examined. Sixteen (16%) in the aortic and 24 (25%) in the mitral position were associated with clinical signs of regurgitation. A phased array system (Hewlett-Packard A77020A) with a 2.5 MHz duplex and 1.9 MHz continuous wave transducer was used. Colour flow mapping showed trivial transvalvar regurgitation in 23 (53%) metal aortic prosthesis, and only nine (20%) metal mitral prostheses. This difference was probably attributable to shielding of the left atrium by the metal components. Colour mapping confirmed abnormal regurgitation in all aortic prostheses with early diastolic numbers, but regurgitation was also shown in 25 (29%) with no diastolic murmur. Abnormal mitral regurgitation was found in 13 (54%) patients with a pansystolic murmur, but also in six (8%) with no systolic murmur. Two patients, thought on clinical grounds to have mild mitral regurgitation, had unexpectedly large jets on colour flow mapping. About one in three prostheses had paraprosthetic leaks, 65 (79%) of which were small with a jet area less than 20% of the area of the receiving chamber. The development of new paraprosthetic leaks led to the diagnosis of bacterial endocarditis in two patients. In eight patients regurgitation was first diagnosed with continuous wave Doppler, but was afterwards shown with colour mapping and in a further 10 regurgitation could only be shown by continuous wave Doppler.(ABSTRACT TRUNCATED AT 250 WORDS)